A PBX1 transcriptional network controls dopaminergic neuron development and is impaired in Parkinson's disease. (28th June 2016) - Villaescusa, J Carlos; Li, Bingsi; Toledo, Enrique M; Rivetti di Val Cervo, Pia; Yang, Shanzheng; Stott, Simon RW; Kaiser, Karol; Islam, Saiful; Gyllborg, Daniel; Laguna‐Goya, Rocio; Landreh, Michael; Lönnerberg, Peter; et al.
Abstract: Pre‐B‐cell leukemia homeobox (PBX) transcription factors are known to regulate organogenesis, but their molecular targets and function in midbrain dopaminergic neurons (mDAn) as well as their role in neurodegenerative diseases are unknown. Here, we show that PBX1 controls a novel transcriptional network required for mDAn specification and survival, which is sufficient to generate mDAn from human stem cells. Mechanistically, PBX1 plays a dual role in transcription by directly repressing or activating genes, such as Onecut2 to inhibit lateral fates during embryogenesis, Pitx3 to promote mDAn development, and Nfe2l1 to protect from oxidative stress. Notably, PBX1 and NFE2L1 levels are severely reduced in dopaminergic neurons of the substantia nigra of Parkinson's disease (PD) patients and decreased NFE2L1 levels increases damage by oxidative stress in human midbrain cells. Thus, our results reveal novel roles for PBX1 and its transcriptional network in mDAn development and PD, opening the door for new therapeutic interventions. Synopsis: PBX1 controls a novel transcriptional network required for midbrain dopaminergic specification and survival. PBX1 and its target NFE2L1 protect dopaminergic neurons from oxidative stress, and their levels are severely reduced in the substantia nigra of Parkinson's disease patients. Pbx1 is expressed in a subpopulation of dopaminergic neuroblasts and controls the specification and survival of midbrain dopaminergic neurons. PBX1 plays a dual role in transcription by directly repressing or activating genes, such as Onecut2 to inhibit lateral fates during embryogenesis, Pitx3 to promote mDAn development, and Nfe2l1 to protect from oxidative stress. PBX1 and NFE2L1 protect dopaminergic neurons from oxidative stress. Nuclear PBX1 and NFE2L1 levels are severely reduced in midbrain dopaminergic neurons of Parkinson's disease patients. Abstract : The homeobox factor PBX1 directly represses or activates key genes involved in specification, survival, and oxidative stress protection of midbrain dopaminergic neurons.